The Relationship Between Maternal Education and Children's Academic Outcomes: A Theoretical Framework. Issue 1 (February 2015) - Harding, Jessica F.; Morris, Pamela A.; Hughes, Diane
<x xml:space="preserve">Abstract</x> The importance of maternal education for children's academic outcomes is widely recognized, and yet the multiple potential mechanisms that explain this relationship are underexplored. The authors integrate theories of human, cultural, and social capital with 2 developmental psychology theories—bioecological theory and developmental niche theory—to draw attention to how maternal education may influence children's academic outcomes through a range of parenting mechanisms, some of which have been largely neglected in research. This framework provides a more complete picture of how maternal education shapes proximal and distal influences on children's academic outcomes and the ways in which these mechanisms interact and reinforce one another across time and context. The implications of this framework for future family research are then discussed.